The acute effect of lower-limb warm-up on muscle performance - Pinfold, S. C.; Harnett, M. C.; Cochrane, D. J. (Research in Sports Medicine, 2018)
It has been purported that the mechanism for muscular improvement after a gluteal warm-up protocol is likely to occur from neural activation. However, little is known about whether changes in muscular performance are due to changes in muscle activity. Therefore, the aim of this study was to determine whether a lower-limb warm-up that targets the gluteal muscle group would improve countermovement jump and short-distance sprinting through increased muscle activity. Ten semi-professional rugby union players (age 25.4 ± 2.9 yr; height 1.83 ± 6.7 m; body mass 96.8 ± 10.6 kg) with at least three years of resistance training experience volunteered for the study. In a cross-over design, participants performed countermovement jumps and 5 m sprints before and after a gluteal warm-up and a 10 min rest (control). Electromyography was used to measure muscle activity of the gluteus maximus and biceps femoris. Countermovement jump height significantly improved (7.9%, p < 0.05) after the lower-limb warm-up protocol compared with the control (3.2%). There was a significant (p < 0.05) improvement in sprint times over 2.5 m and 5 m regardless of the condition. There was no significant change in the muscle activity in any of the conditions. The results indicate that a lower-limb warm-up can acutely enhance countermovement jump performance compared to a control.